THE EFFECT OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER LOYALTY AT CV. ANUGRAH JAYA ABADI - Sugiono Sugiono; Dede Dede; Hikmatul Aliyah; Krismawan Ernetus (Journal of Research in Social Science and Humanities, 2025)
The purpose of this study is to understand the impact of product and service quality on customer loyalty at CV Anugrah Jaya Abadi in Bandar Lampung. Latar belakang penelitian ini was based on the importance of maintaining customer loyalty in a robust business environment. Good product quality and customer service that is always helpful are the two main factors that encourage customers to continuously buy products and recommend businesses to others.The research methodology that is being used is a quantitative approach using survey data. Data is collected through questionnaires given to 100 CV Anugrah Jaya Abadi respondents. Analisis data dilakukan dengan using regresi linier berganda untuk menguji pengaruh simultan dan parsial antara variabel independen (kualitas product dan kualitas pelayanan) terhadap variabel dependen (loyalitas pelanggan). The study's findings indicate that product and service quality simultaneously have a significant impact on customer loyalty. For example, when it comes to fostering customer loyalty, product quality has a greater impact than service quality. This highlights how important it is for businesses to continuously monitor and improve their product quality while providing customers with first-rate service.Therefore, it is hoped that CV Anugrah Jaya Abadi will be able to be used as a guide in developing strategies to improve product quality and customer loyalty in a comprehensive manner.